Relation of Morphology and Karyotype in Doritis spp. and Their Hybrid - รุ่งรัชกานนท์ กาญจนา; พลเยี่ยม แสงเดือน; สุภาพรม ถาวร (KKU Science Journal, 2013)
Doritis pulcherrima, Dor. pulcherrima var. chumpornensis, Dor. pulcherrima var. buyssoniana and a hybrid of Dor. pulcherrima var. buyssoniana x Dor. pulcherrima had the same morphology of leaves and stems but a difference in morphology of flowers. The karyotypes of Dor. pulcherrima and Dor. pulcherrima var. chumpornensis were similar with chromosome numbers of 2n = 2x = 38 with chromosome patterns of 6M + 24Sm + 8A and 8M + 22Sm + 8A, respectively. Dor. pulcherrima var. buyssoniana was a tetraploid (2n = 4x = 76) with a chromosome pattern of 12M + 48Sm + 16A. The hybrid Dor. pulcherrima var. buyssoniana x Dor. pulcherrima was a triploid (2n = 3x = 57) with a chromosome pattern of 9M + 36Sm + 12A. Normal bivalents in meiosis of Dor. pulcherrima var. buyssoniana showed that it was an allotetraploid species.